2017
DOI: 10.1186/s12889-017-4366-9
|View full text |Cite
|
Sign up to set email alerts
|

Solid medical waste: a cross sectional study of household disposal practices and reported harm in Southern Ghana

Abstract: BackgroundSolid medical waste (SMW) in households is perceived to pose minimal risks to the public compared to SMW generated from healthcare facilities. While waste from healthcare facilities is subject to recommended safety measures to minimize risks to human health and the environment, similar waste in households is often untreated and co-mingled with household waste which ends up in landfills and open dumps in many African countries. In Ghana, the management of this potentially hazardous waste stream at hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 32 publications
5
28
0
1
Order By: Relevance
“…All healthcare and domestic wastes were mixed together, there was no available enforced law, low vaccination rates among the HCP, PPE was unavailable or partially used, staff training was inadequate, and high rates of NSIs were reported, especially among waste workers. Similar results in terms of poor HCWM have been reported by previous studies in many African countries [76][77][78][79]. Such poor HCWM will result in serious health effects to the population and also has negative impacts on the environment [6,52].…”
Section: Discussionsupporting
confidence: 84%
“…All healthcare and domestic wastes were mixed together, there was no available enforced law, low vaccination rates among the HCP, PPE was unavailable or partially used, staff training was inadequate, and high rates of NSIs were reported, especially among waste workers. Similar results in terms of poor HCWM have been reported by previous studies in many African countries [76][77][78][79]. Such poor HCWM will result in serious health effects to the population and also has negative impacts on the environment [6,52].…”
Section: Discussionsupporting
confidence: 84%
“…This has public wellbeing, ecosystem, and economic implications for the citizens and the healthcare delivery system at large (34). In contrast, earlier studies conducted in Nigeria (6,35) and other countries (22,26,27,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) had identified discarding in the household garbage as the most common means of disposal of unused/unwanted medicines. Moreover, an online-based survey conducted in Turkey reported that 34.0% of the respondents returned unused medicines to the health facility (48).…”
Section: Discussionmentioning
confidence: 97%
“…Data was collected in two phases within a larger study investigating solid medical waste from non-traditional sources in the community. The first phase involved a household survey to identify household disposal practices regarding SMW and the second phase involved a household waste audit [12]. Correspondingly, the FGDs and interviews were conducted in June/July, 2014 and January/February, 2015.…”
Section: Study Area and Participantsmentioning
confidence: 99%
“…There is a dearth of literature describing the management of SMW from community sources in Ghana. To address this, a qualitative evaluation was undertaken within a larger study investigating the management of SMW at community level [12]. We present the perceptions and practices of household members, TBAs and CS regarding disposal and potential harm from SMW in the community.…”
Section: Introductionmentioning
confidence: 99%